Cybersecurity Challenges in the Electric Vehicle Industry: A Technical Overview - Raghukumar Bommenahalli (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of electric vehicle (EV) technology and charging infrastructure has introduced unprecedented cybersecurity challenges across the automotive sector. This article examines the current state of cybersecurity in the electrification industry, focusing on the challenges faced by EV manufacturers and charging infrastructure operators. The article reveals significant vulnerabilities in charging station security, ranging from hardware security modules to communication protocols and payment systems. The article explores the regulatory landscape, implementation challenges, and the impact on various stakeholders including manufacturers, suppliers, and end users. The article highlights the critical need for standardized security frameworks, improved incident response capabilities, and strategic investments in cybersecurity infrastructure. The article demonstrates that organizations implementing comprehensive security measures achieve substantial improvements in threat detection and incident prevention, while those lacking robust security frameworks face increased risks of breaches and operational disruptions.